Idea e identità collettiva. Alcune considerazioni sul pensiero di José Ortega y Gasset - Visone, Tommaso (SocietàMutamentoPolitica, 2013)
This article analyzes the concepts of “Nation” and “Collective life” in the Ortega y Gasset thought with the aim to stress the features of their relation and their importance for the current debate on collective identity. In order to do that this paper actually tries to examine the impact of “ideas” and “ideologies”, notions created by the Spanish philosopher on the constructive dynamics that rule the lives of collective identities.